Immobilized Polydiacetylene Lipid Vesicles on Polydimethylsiloxane Micropillars as a Surfactin-Based Label-Free Bacterial Sensor Platform - Jannah, Fadilatul; Kim, Jung-Hoon; Lee, Jin-Won; Kim, Jong-Man; Kim, Jung-Mogg; Lee, Haiwon (Frontiers in Materials, 2018)
Accurate detection and sensing of bacteria are becoming increasingly important not only in microbiology but in a variety of fields including medicine, food, public health, and environmental science. However, even new rapid methods are not convenient enough. Here, we describe a simple and efficient label-free bacterial detection system using the polydiacetylene (PDA) liposomes immobilized on the 3D polydimethylsiloxane (PDMS) micropillars. Our system utilizes the colorimetric response of amine functionalized PDA vesicles to surfactin, a bacterial cyclic lipopeptide commonly released by Gram-positive Bacillus species as an antibiotic. To improve the sensitivity of PDA vesicles to surfactin by increasing the number and surface area of immobilized vesicles, the PDA vesicles were immobilized on the micropillar structure to give a hierarchical 3D PDA vesicle structure. For the fabrication of the 3D micropillar structure, polydimethylsiloxane (PDMS) was used to overcome the limitations imposed by silicon-based fabrication. In contrast to the 2D-PDA-PDMS system, which could only hardly detect the presence of 500 µM surfactin, the 3D-PDA-PDMS system could efficiently detect the presence of 5 µM surfactin and the initial presence of 4 x 101 cells/ml of Bacillus subtilis NCIB3610, which actively produces surfactin. Furthermore, bacterial strains that are known to produce no surfactin, such as Staphylococcus aureus Newman, Escherichia coli DH5, and Pseudomonas aeruginosa PA14 were not detected by our system suggesting that the 3D-PDA-PDMS system is highly specific to surfactin but not to other chemicals produced by bacteria. Taken together, our results suggest that the 3D-PDA-PDMS system can sensitively and selectively be used for the high throughput detection and screening of biotechnologically important surfactin-producing bacterial strains.